Piperlongumine Attenuates High Calcium/Phosphate-Induced Arterial Calcification by Preserving P53/PTEN Signaling - Shi, Wenxiang; Lu, Jieyu; Li, Junhan; Qiu, Ming; Lu, Yan; Gu, Jia; Kong, Xiangqing; Sun, Wei (Frontiers in Cardiovascular Medicine, 2021)
Vascular calcification frequently occurs in the process of chronic kidney disease, atherosclerosis and aging, resulting in an increased prevalence of cardiovascular events. Piperlongumine (PLG) is a natural product isolated from Piper longum L. Here, we aimed to explore the effect of PLG in high calcium- and phosphate-induced vascular calcification and the associated mechanism. Flow cytometry assays showed that PLG at concentrations less than 10 μM did not promote vascular smooth muscle cell (VSMC) apoptosis, and PLG at concentrations greater than 2.5 μM inhibited VSMC proliferation. Thus, 2.5 μM PLG was selected for subsequent experiments. Alizarin red staining and ALP activity assays showed that PLG inhibited calcium deposition of VSMCs treated with high calcium/phosphate medium. PLG also decreased the expression of osteogenic genes and proteins, including Runx2, Bmp2 and OPN, as determined by qPCR and western blotting. In a vitamin D-induced aortic calcification mouse model, a 5 mg/kg dose of PLG decreased calcium deposition in the aortic wall as well as Runx2 expression. With regard to the mechanism, we found that the levels of P53 mRNA and protein in both VSMCs and mouse aortic tissues were decreased in the calcification models, and we observed that PLG preserved the levels of P53 and its downstream gene PTEN. Concurrent treatment of VSMCs with P53 ShRNA and PLG blunted the anti-calcific effect of PLG. In conclusion, PLG attenuates high calcium/phosphate-induced vascular calcification by upregulating P53/PTEN signalling in VSMCs. PLG may act as a promising herbal extract for the clinical management of vascular calcification.